The Institutional and Operational Challenges of the Regional Intelligence Community (KOMINDA) in Supporting National Security Stability in Indonesia - Franziska Zeligke; Stanislaus Riyanta (Universitas KH. Abdul Chalim Mojokerto, 2026)
This article analyzes the challenges in task execution faced by the Regional Intelligence Community (Kominda) institution in supporting national security stability in the regions, as well as the efforts that can be undertaken to address these challenges. This research is fundamentally based on Article 30 of Law No. 17 of 2011 concerning State Intelligence, which asserts the critical importance of inter-agency coordination to maintain the security and order of the nation, as well as the Minister of Home Affairs Regulation No. 16 of 2011 concerning Kominda, which emphasizes Kominda’s strategic role in the early detection of potential threats as an integral part of the national intelligence system. However, in practice, the implementation of Kominda's duties and functions continues to encounter a variety of challenges that have not been systematically mapped. This study aims to comprehend the factors inhibiting the effectiveness of Kominda’s task execution in contributing to the strengthening of national resilience in a sustainable manner. The research employs the Institutional Capacity Theory approach, which emphasizes the importance of organizational structure, resources, and legitimacy in shaping the performance of public institutions. This research is expected to offer strategic recommendations for Kominda's institutional improvement, particularly regarding coordination mechanisms, human resource capacity, and budgetary support, thereby serving as a crucial policy reference for developing a professional, adaptive, and accountable intelligence apparatus.